2013
DOI: 10.1021/nn404448s
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Selection of Biomineralizing DNA Aptamers Using Deep Sequencing and Population Clustering

Abstract: DNA-based information systems drive the combinatorial optimization processes of natural evolution, including the evolution of biominerals. Advances in high-throughput DNA sequencing expand the power of DNA as a potential information platform for combinatorial engineering, but many applications remain to be developed due in part to the challenge of handling large amounts of sequence data. Here we employ high-throughput sequencing and a recently developed clustering method (AutoSOME) to identify single-stranded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 35 publications
2
35
0
Order By: Relevance
“…Aptamer candidates can be determined by the highthroughput sequencing at much earlier cycles of a selection starting from the naïve/non-enriched pool itself whereas the cloning based aptamer identification obliges evolution of the selection pool down to a few sequences. Consistent with the theory, Bawazer et al 71 implemented the sequence similarity (motifs or consensus sequences) and the high abundance rate of the sequences in the aptamer selection, in which aptamers specific to zinc oxide (ZnO) semiconductor mineral surfaces (bio-mineralizing DNA aptamers, facilitating ZnO mineralization from a hydrated Zn(NO3)2 precursor) For instance, Wilson et al 27 recently reported bivalent thrombin aptamers selected at single cycle using 454 GS FLX NGS platform that enabled comprehensive data analysis obtained from the sequential dissociation rounds.…”
Section: Next Generation Sequencing-based Methodssupporting
confidence: 55%
“…Aptamer candidates can be determined by the highthroughput sequencing at much earlier cycles of a selection starting from the naïve/non-enriched pool itself whereas the cloning based aptamer identification obliges evolution of the selection pool down to a few sequences. Consistent with the theory, Bawazer et al 71 implemented the sequence similarity (motifs or consensus sequences) and the high abundance rate of the sequences in the aptamer selection, in which aptamers specific to zinc oxide (ZnO) semiconductor mineral surfaces (bio-mineralizing DNA aptamers, facilitating ZnO mineralization from a hydrated Zn(NO3)2 precursor) For instance, Wilson et al 27 recently reported bivalent thrombin aptamers selected at single cycle using 454 GS FLX NGS platform that enabled comprehensive data analysis obtained from the sequential dissociation rounds.…”
Section: Next Generation Sequencing-based Methodssupporting
confidence: 55%
“…This may explain why the above aptamers are made of simple repeating sequences. [11,12] Therefore,i nstead of performing aptamer selections,D NA homopolymers might be ag ood starting point for surface-binding DNA. Herein, we communicate aquite surprising yet useful finding that poly-cytosine (poly-C) DNAbinds strongly to many common inorganic surfaces.…”
mentioning
confidence: 99%
“…Gerdon and co‐workers used a precipitation SELEX method to isolate DNA aptamers for calcium phosphate . A single round of aptamer selection was performed by Morse and co‐workers on ZnO, and a simple T 30 DNA sequence was concluded to be its aptamer . By a screening method, however, poly‐C DNA was found to adsorb more strongly than poly‐T DNA .…”
Section: Surface Binding Aptamers From Selectionmentioning
confidence: 99%
“…With a high surface binding affinity, such DNA can also be useful for controlling the growth of nanoparticles. For example, attempts have been made with mineralization using ZnO . The much more systematically studied examples are the growth of gold nanostructures (Figure C) .…”
Section: Application Of Surface Binding Dna Sequencesmentioning
confidence: 99%
See 1 more Smart Citation